0

# how solve (m^2-4m+3)

its answare is m=0,1,3

### 1 Answer by Expert Tutors

Marietta G. | Versatile EducatorVersatile Educator
4.8 4.8 (186 lesson ratings) (186)
0
m2-4m+3 = 0

First Factor the Trinomial:  m2-4m+3
Trinomials have 3 terms. The 3 terms of this trinomial are: m2, -4m, and +3.
Trinomials are formed by multiplying 2 binomials together. Binomials have 2 terms.
1.  (      )(      )

2. Factor the first term m2 = m x m
(m   )(m    )

3. The coefficient of the second term -4m, is -4
formed by adding the factors of the third term.

4. The third term +3 has the factors 1, 3   or -1, -3.
The pair of factors which add to give -4, is -1,-3

5. This gives the factors:
(m - 1 )(m - 3)

Solve the Trinomial
To solve this trinomial we must let it be = 0
m2-4m+3      = 0
(m - 1 )(m - 3)= 0

If (m - 1 )(m - 3)= 0    then at least 1 factor must be 0
Taking the first factor (m - 1):
if m-1 =  0
m-1 =  0
+1 =+1
m = 1

if m-3 = 0
m-3 = 0
+3 =+3
m = 3

The solution to the problem: m = 1, 3    NOT m = 0